Trends in educational inequalities in obesity in 15 European countries between 1990 and 2010 - Kristina Hoffmann; Rianne De Gelder; Yannan Hu; Matthias Bopp; Jozsef Vitrai; Eero Lahelma; Gwenn Menvielle; Paula Santana; Enrique Regidor; Ola Ekholm; Johan P. Mackenbach; Frank J. van Lenthe (BMC, 2017)
Abstract Background The prevalence of obesity increased dramatically in many European countries in the past decades. Whether the increase occurred to the same extent in all socioeconomic groups is less known. We systematically assessed and compared the trends in educational inequalities in obesity in 15 different European countries between 1990 and 2010. Methods Nationally representative survey data from 15 European countries were harmonized and used in a meta-regression of trends in prevalence and educational inequalities in obesity between 1990 and 2010. Educational inequalities were estimated by means of absolute rate differences and relative rate ratios in men and women aged 30-64 years. Results A statistically significant increase in the prevalence of obesity was found for all countries, except for Ireland (among men) and for France, Hungary, Italy and Poland (among women). Meta-regressions showed a statistically significant overall increase in absolute inequalities of 0.11% points [95% CI 0.03, 0.20] per year among men and 0.12% points [95% CI 0.04, 0.20] per year among women. Relative inequalities did not significantly change over time in most countries. A significant reduction of relative inequalities was found among Austrian and Italian women. Conclusion The increase in the overall prevalence aligned with a widening of absolute but not of relative inequalities in obesity in many European countries over the past two decades. Our findings urge for a further understanding of the drivers of the increase in obesity in lower education groups particularly, and an equity perspective in population-based obesity prevention strategies.